Yaw stability control of articulated frame off-highway vehicles via displacement controlled steer-by-wire. (December 2015) - Daher, Naseem; Ivantysynova, Monika
Abstract: Off-highway vehicles have not received the same level of scrutiny that their on-highway counterparts did relative to safety, comfort, fuel economy, and automation. Over the past few decades, various active chassis safety control systems, architectures, and schemes have been researched and developed to improve the stability and handling of on-highway vehicles, including articulated vehicles such as tractor–trailer applications. In this paper, the authors investigate a yaw stability control system for articulated frame steering off-highway vehicles via novel steer-by-wire technology that they have recently developed. A high-fidelity vehicle dynamics model is derived while keeping the yaw rate decoupled from the lateral acceleration, in order to separate the primary path-following task (driver) from the secondary disturbance–attenuation task (controller). The control algorithm is then designed such that the two tasks do not hamper one another, and that the automatic controller is quickly activated for a short period of time to counteract instabilities, and then smoothly relinquishes control back to the human operator. Simulation and experimental testing results are obtained to validate the vehicle dynamics model, the control algorithm design, and the new system's efficacy in counteracting yaw instabilities on low-friction surfaces using standard vehicle dynamic maneuvers. Graphical abstract: Highlights: A yaw stability controller is developed for an articulated frame steering vehicle. Vehicle dynamics model decouples yaw rate from lateral acceleration. Path-following (driver) is separated from disturbance–attenuation (controller). Controller is validated in simulation and experimentally on a prototype machine. Adequate controller performance/robustness under various maneuvers and conditions.